A Review of Behaviorist Learning Theory and its Impact on the Learning Process in Schools - Alfajri Yusra; Neviyarni S; Erianjoni Erianjoni (International Journal of Educational Dynamics, 2022)
Behavioristic learning theory and its influence on learning and the learning process are discussed in this article. According to behavioristic theory, learning results in behavior modification. Behavioristic learning theories are hypotheses about how people learn, and they argue that rewards and reinforcement play a role in learning. According to this belief, the behavior will stop if it receives punishment. The expression "stimulus-response" is used in behavioristic learning theory to describe how a stimulus, or a stimulus in the form of rewards, reinforcement, and punishment, will produce a reaction. The behavior may persist or cease in response. This behavioristic hypothesis is studied by psychologists who view behavior change as evidence of learning. Despite receiving a lot of support and criticism, the behavioristic theory still has an impact on the teaching strategies used during the teaching and learning process.